Nasal Obstruction as a Potential Factor Contributing to Hypoxemia in Obstructive Sleep Apnea - Lan MC (Dove Medical Press, 2021)
Ming-Chin Lan,1,2 Ming-Ying Lan,3,4 Edward C Kuan,5 Yun-Chen Huang,1,2 Tung-Tsun Huang,1,2 Yen-Bin Hsu3,4 1Department of Otolaryngology-Head and Neck Surgery, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, Taiwan; 2School of Medicine, Tzu Chi University, Hualien, Taiwan; 3Department of Otolaryngology-Head and Neck Surgery, Taipei Veterans General Hospital, Taipei, Taiwan; 4School of Medicine, National Yang-Ming University, Taipei, Taiwan; 5Department of Otolaryngology-Head and Neck Surgery, University of California, Irvine, Orange, CA, USACorrespondence: Yen-Bin HsuDepartment of Otolaryngology-Head and Neck Surgery, Taipei Veterans General Hospital, No. 201, Sec. 2, Shipai Road, Beitou District, Taipei City 11217, TaiwanTel +886-2-28741210Fax +886-2-28757338Email yenbinhsu@gmail.comPurpose: This study aimed to evaluate the correlation between nasal resistance and oxygen desaturation to better elucidate the role of nasal obstruction in the pathophysiology of obstructive sleep apnea (OSA).Patients and Methods: Eighty-eight OSA patients aged between 22 and 77 years were enrolled in this study. Nasal resistance was measured at pressures of 75, 150, and 300 Pa, with the patients first in the seated position than in the supine position. Relationships between the oximetric variables and nasal resistance in the seated and supine positions were analyzed.Results: From seated to supine position, a statistically significant increase in nasal resistance was observed at pressures of 75 and 150 Pa (p=0.001 and p=0.006, respectively). Significant positive correlations were noted between nasal resistance in the supine position at 75 Pa (SupineNR75) and oximetry variables, including oxygen desaturation index (ODI, p=0.015) and the percentage of total time with oxygen saturation level lower than 90% (T < 90%, p=0.012). However, significant positive correlations existed only in moderate to severe OSA when the study group was further divided into two subgroups (mild vs moderate to severe OSA). Body mass index (β = 0.476, p< 0.001) and SupineNR75 (β = 0.303, p=0.004) were identified as independent predictors for increased ODI.Conclusion: Nasal resistance in the supine position measured at 75 Pa significantly correlated with the severity of oxygen desaturation. Therefore, nasal obstruction may play an important role in the pathophysiology of hypoxemia in OSA patients, especially in patients with moderate to severe OSA.Keywords: nasal resistance, rhinomanometry, polysomnography, OSA